Transcriptional Pathways Associated with Skeletal Muscle Changes after Spinal Cord Injury and Treadmill Locomotor Training. (24th August 2015) - Baligand, Celine; Chen, Yi-Wen; Ye, Fan; Pandey, Sachchida Nand; Lai, San-Huei; Liu, Min; Vandenborne, Krista
Abstract : The genetic and molecular events associated with changes in muscle mass and function after SCI and after the implementation of candidate therapeutic approaches are still not completely known. The overall objective of this study was to identify key molecular pathways activated with muscle remodeling after SCI and locomotor training. We implemented treadmill training in a well-characterized rat model of moderate SCI and performed genome wide expression profiling on soleus muscles at multiple time points: 3, 8, and 14 days after SCI. We found that the activity of the protein ubiquitination and mitochondrial function related pathways was altered with SCI and corrected with treadmill training. The BMP pathway was differentially activated with early treadmill training as shown by Ingenuity Pathway Analysis. The expression of several muscle mass regulators was modulated by treadmill training, including Fst, Jun, Bmpr2, Actr2b, and Smad3 . In addition, key players in fatty acids metabolism ( Lpl and Fabp3 ) responded to both SCI induced inactivity and reloading with training. The decrease in Smad3 and Fst early after the initiation of treadmill training was confirmed by RT-PCR. Our data suggest that TGF β /Smad3 signaling may be mainly involved in the decrease in muscle mass observed with SCI, while the BMP pathway was activated with treadmill training.